THE ROLE OF VALUES IN THE SPIRITUAL PERFECTION OF SOCIETY - Bayeshanov Abdulla Mustafayevich (Sciental Journals Publishing, 2025)
This article explores the role of values in the spiritual perfection of society, with particular attention to the historical roots of the culture of the peoples of Central Asia, especially the Uzbek nation. It examines the social, philosophical, moral, religious, and artistic worldviews and ideas embedded in national values, and highlights their significance in shaping a morally rich and spiritually advanced society.
Keywords: National identity, values, morality, social ethics, oral folklore, fairy tales, legends